The Armenian-Russian Military-Political Cooperation System and the 102 nd Military Base of Russia - Ghevondyan, Alen (History and Culture, 2025)
Armenian-Russian strategic cooperative relations have traditionally been, and continue to be, one of the most important components of geopolitical processes in the South Caucasus. These relations have historically reflected the interests and approaches of both states during the early period of independence and throughout subsequent geopolitical developments in the region.This article examines the nature of cooperation with the Russian Federation in ensuring the security of the Republic of Armenia (RA) and its various formats. Special attention is given to the different aspects of military-political interactions between the two countries. The article discusses areas such as political and legal treaties, military-technical cooperation, and defense policy planning within the framework of Armenian-Russian strategic cooperation and alliance relations. The concept of "strategic cooperation" is analyzed from a conceptual standpoint, as it has traditionally been used to define the relationship between the Republic of Armenia and the Russian Federation.A separate discussion is dedicated to the structural and functional characteristics of the Russian Federation's 102-th military base, where the analysis concludes that it functions as a joint unit equipped with military hardware and personnel capable of addressing a variety of military tasks.The article also presents the view that tensions in cooperative relations between superpowers and smaller states often arise due to differing perceptions of interests. These differences, rooted in the varying scales of resources and geopolitical realities, lead to divergent approaches to shared concerns in evolving geopolitical contexts.
Keywords: 102-th military base; Armenian-Russian relations; strategic partnership; South Caucasus; military-political cooperation; military equipment; balance of power; military-technical cooperation